Can the digital economy development curb carbon emissions? Evidence from China - Hao, Xiaoli; Wen, Shufang; Li, Yuhong; Xu, Yuping; Xue, Yan (Frontiers in Psychology, 2022)
"Carbon neutrality, carbon peaking" is China's national commitment to the whole world about its plans to manage global climate change. China faces many severe challenges in fulfilling its commitments to reduce emissions. China's digital economy is currently booming, and whether it can provide opportunities for reducing regional carbon emissions is worth exploring. This study constructed a comprehensive system to evaluate the development of its digital economy based on China's regional data and empirically tested the direct, indirect and spatial effects of the comprehensive development of digital economy on regional carbon emissions. In addition, it examined the special stage characteristics using a Hansen threshold model. This study found the following: First, the digital economy significantly suppresses carbon emissions in general, notably with a spatial spillover effect to neighboring provinces. Secondly, an analysis of the mechanism shows that the comprehensive development of a digital economy can restrain regional carbon emissions through industrial progress and the optimization of energy consumption. Third, there are double thresholds, special driving trends and an "inverted N-type" relationship with development. Fourth, a spatial heterogeneity analysis revealed that significant "local" and "neighboring" impacts on the reduction of carbon emissions only exist in the central and eastern areas. This study has a reference value for releasing the dividend of digital economy development and reducing carbon emissions.